Design tools for rapid multidomain prototyping of power electronic systems - Evans, Paul L.; Castellazzi, Alberto; Johnson, C. Mark (IEEE, 2016)
The need for multidisciplinary virtual prototyping in power electronics has been well established however design tools capable of facilitating a rapid, iterative virtual design process do not exist. A key challenge in developing such tools is identifying and developing modelling techniques which can account for 3D, geometrical design choices without unduly affecting simulation speed. This challenge has been addressed in this work using model order reduction techniques and a prototype power electronic design tool incorporating these techniques is presented. A relevant electro-thermal power module design example is then used to demonstrate the performance of the software and model order reduction techniques. Five design iterations can be evaluated, using 3D inductive and thermal models, under typical operating and startup conditions on a desktop PC in less than 15 minutes. The results are validated experimentally for both thermal and electrical domains.